New Managerialism in Czechoslovakia and the Soviet Union - Prasad, Shailendra (Academy of Management Journal, 1966)
Significant changes are introduced in Czech and Russian Enterprise management as part of the economic reforms, particularly in enterprise goals and decentralization of managerial authority. This paper reviews major aspects of this new managerialism and hints that there may be a ?theory of convergence? in the making in communist countries.